STRATEGI PEMBELAJARAN PARTISIPATIF BAGI BELAJAR ORANG DEWASA (PENDEKATAN ANDRAGOGI) - Sujarwo Sujarwo (MAJALAH ILMIAH PEMBELAJARAN, 2007)
In educational perspective, adult’s purposes for learning are to achieve goals and affirm identity. Therefore, participation in adult learning has positive effects in improving quality of life. In andragogy, learning is not merely knowledge transfer but it also should be able to improve confidence that students are capable to perform well in their life.Andragogy sees students as individuals with self-concept, which is independent. Adults have many experiences that will become rich learning resources. Adult’s readiness to study is relevant to the problem that they face. Learning is oriented to meet their needs.The implications of participative learning strategy are: (1) learning atmosphere is adjusted to the characteristics and needs. Learning atmosphere encourages student to have initiatives and flexible. (2) Students are involved in determining the learning needs and outcome. (3) Learning activities involved students actively. (4) Learning evaluations use more self-evaluation.